El estado de la investigación sobre marketing ecológico en Espa\~na: Análisis de revistas Espa\~nolas 1993 - 2003 - A. Chamorro Mera; F. J. Miranda González; S. Rubio Lacoba (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
The fundamental aim of this article is to describe the importance of the research on green marketing in Spain. With this in mind, we analyze the main studies published during the decade 1993-2003, observing the topic of the research on each article, the methodology and analytical techniques used and other relevant aspects of the research. This will help us to further existing knowledge in the field of green marketing and allow us to suggest possible lines of research for the near future.
Keywords: 330; environmental consumer; green marketing; sustainable marketing; state of the research; environmental communication